The study of readiness factors of UniSZA’s students towards the Massive Open Online Courses (MOOC) implementation through their perception / Nur Hayatul Nisab Mat Sarip - Mat Sarip, Nur Hayatul Nisab (Bachelor of Science (Hons.) Statistics, 2015)
The Massive Open Online Courses (MOOC) is one of the recent innovation of e-learning. This study was carried out on respondent in Universiti Sultan Zainal Abidin, UniSZA in Kuala Terengganu with the aim to identify the readiness factors for the students towards the MOOC implementation. Objective of this study was to investigate relationship between factors (Technology Access, Online Skills and Relationship and Learning Style and motivation) student’s perception on MOOC implementation. This study was based on simple random sampling method and the data was obtained through questionnaires distribution. There were 214 respondents that have been chosen in this study. Questionnaires were distributed and the data gathered was analysed to derive possible findings of the study. AMOS version 18 program and Statistical Package for Social Science (SPSS) software, version 21 have been used to analyse the data.The study revealed that all the readiness factors were significant to the study. It was found that the factor of Technology Access give the lowest significancy to the study. The study also stated that the percentage of studen’st awareness towards the MOOC implementation is higher